Youth international volunteering in the context of social work - Neringa Paulauskytė; Neringa Povilaitienė (Taikomieji Moksliniai Tyrimai)
The article analyzes the peculiarities of youth voluntary work when choosing and carrying out voluntary activities in foreign countries in the context of the field of social work. The sources of scientific information about the motivations for choosing volunteering, international volunteering activities and the social benefits created by volunteering have been examined. The internal and external motives that encourage volunteers to choose voluntary activities in foreign countries have been investigated, the social benefits of international volunteering have been clarified and the challenges of volunteers in international volunteering have been revealed. Research methods: a qualitative study was conducted in order to investigate youth international social work volunteering. Structured interview was used as a data collection method, qualitative content analysis method was used to process the research data. Research sample: 6 volunteers were interviewed during the research.